Bone pathology inpsoriatic arthritis - V. V. Badokin (Научно-практическая ревматология)
Objective. To study different variants of osteolysis in pts with psoriatic arthritis (PA) and to reveal their relationship with other clinico-radiological features of joint damage. Material and methods. 370 pts with definite PA having different variants of joint damage were included. Radiological examination of bones and joints (in some cases large picture frame) was performed. Morphological evaluation of synovial biopsies was done in 34 pts with PA and 10 pts with rheumatoid arthritis (RA). Results. Different types of osteolysis were revealed in 80 (21,6%) pts. Osteolytic variant of joint damage was present in 29 pts. 33 pts had acral, 48 — intra-articular osteolysis and 16 - true bone atrophy. Frequency and intensity of bone resorption were associated with severity of PA. Acral osteolysis correlated with arthritis of distal interphalangeal joints and onychodystrophy. Intra-articular osteolysis was most often present in distal interphalangeal joints of hands and metacarpophalangeal joints (39,6% and 41,7% respectively). Characteristic feature of PA was combination of prominent resorption with formation of bone ankylosis and periosteal reaction. Ankylosis was present in 33,3% of pts with intra-articular osteolysis and in 60% of pts with combination of different osteolysis variants. Systemic reaction of microcirculation in synovial biopsies was most prominent in osteolytic variant: marked thickening of capillary and venule basal membrane with high level of acid phosphatase, increased capillary and precapillary blood flow with stasis features, vascular lymphocyte and macrophage infiltration, productive vasculitis with annular wall thickening, thrombovasculitis and villi deep layer sclerosis. Conclusion. Different variants of osteolysis show bone involvement in PA. Acral and intra- articular osteolysis association with bone ankylosis and periostitis proves their common pathogenetic entity.